A ascens\~ao chinesa no setor aeroespacial - Alícia Cechin; Scarlett Queen Almeida Bispo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The aerospace sector is highly strategic and symbolizes the economic, technological and geopolitical power of a country. In order to develop "national champions", China has developed policies and strategies for various industries. Thus, while these policies successful, it was possible to notice an acceleration in production, employment and international trade. The accelerated Chinese aerospace development is related to its intention to develop industries with high technological intensity, which has been strongly present in development plans since the end of the 70's. Therefore, the present study aims to analyze the development policies of the Chinese space and aviation industry from the 1950s to the prospects for the coming years, emphasizing the Made in China 2025 (MIC25) Development Plans and the 14th Five-Year Plan (2021-2025), as well as identifying their positioning current in this sector. The findings show China has achieved impressive results in the sector, especially in the space industry, as advances have occurred to a lesser extent in the aviation segment. The aerospace sector remains a key area in the 14th Five-Year Plan, mainly through investments in research and development and financial support from the State, suggesting greater achievements in the future.
Keywords: O1; O14; O3; 330; development policies; China; space; aviation; innovation